Сучасний стан освітніх послуг у сфері вищої аграрної освіти в Україні - Кобець, Анатолій Степанович; Kobets, Anatoly Stepanovich ’, Anatoliy S.; Kobec, A. S.; Kobets, Anatoliy; Kobets, A. S.; Сobets, A.; Пугач, Андрій Миколайович; Pugach, Andrіy (Дні пропет ровський ре гіо нальний інсти тут державного управління Національної академії державного управління при Прези дентові України, 2016)
ї освіти України до європейського освітнього простору та кроки їх впровадження. Проведений аналіз сучасного стану вищої аграрної освіти та аналіз чинної державної політики інтеграції вищої аграрної освіти України до європейського освітнього простору, які дозволили визначити проблемні питання та виокремити напрями її подальшого розвитку. Обґрунтовується необхідність реформування сільськогосподарської освіти, науки одночасно з реформуванням аграрного виробництва. До переваг української системи аграрної освіти віднесено наявність умов для створення і апробації інноваційних продуктів для різних агрокліматичних зон у межах одного регіону, що забезпечує відповідність наукомістких результатів реальним умовам ведення аграрного виробництва. До пропозицій віднесено створення бізнес-інкубаторів для підтримки молодіжних бізнес-проектів, забезпечення можливості проходження довготривалої практики студентів на виробництві, налагодження взаємодії ВНЗ із товаровиробниками, службами зайнятості. Відзначається необхідність реалізації концепції безперервної та багаторівневої аграрної освіти, створення університетів дослідницького типу та розвиток науковонавчальних центрів. Це дозволить забезпечити конкурентоспроможність наукових розробок, створити банк інноваційних розробок, запроваджувати результати НДР на міжнародний ринок наукомісткої продукції. Perspective directions of integration state policy of Ukraine Higher Education into the European educational space and steps of implementation are determined. It is analysed the current state of higher agricultural education and integration current state policy of Ukraine Higher Education into the European educational space which allowed to identify problems and highlighted areas for further development. It is considered that it is necessary to establish cooperation in the triangle «production - education – science», extend the impact of scientists and experts on the content of educational sector, come educational standards to needs and challenges of the real economy, as upgrades of industry standards for higher education, forming curricula, new teaching methods. Professionals training is possible only in a simulation of modern production principles, including the European Union. It is necessary to strengthen the position of agricultural universities as international educational and scientific centers in the framework of the European educational space. This refers to the practice and teaching students abroad, teachers training, participation in international programs, joint research. Ukrainian agricultural education system has competitive advantages despite the general neglect and can be considered unique in the educational market, it has conditions for the creation and testing of innovative products for different agro-climatic zones within a region. This provides the results of knowledge-based real conditions of agricultural production. Among the weaknesses of the education system it is possible to note a lack of cooperation with employers, lack of logistical and information and communication resources, mismatch of modern innovative designs and high technologies. It is therefore necessary to overcome the gap between the content of education and the real needs of innovation economy. In general, you need to ensure long-term practice of passing students into the production, which is an absolute necessity in terms of training of qualified specialists. It is necessary to realize the concept of continuous and multi-level agricultural education focused on the holistic development of the individual, increasing social adaptation in today’s mobile world. It is important to ensure cooperation between higher education institutions from producers, services employment. Key terms of agricultural education European level is to create research universities and development of such scientific and educational centers. This is the way to competitive scientific developments, Bank of innovation, promotion of scientific and research work of local scientists in the international market of high technology products. Ukrainian experts are to be competitive in internal and world market.
Current status of educational services in higher agricultural education in Ukraine
Keywords: освітні послуги; educational services; вища аграрна освіта; public policy; державна політика; public policy; європейський освітній простір; the European educational space